BATAM MSMEs SHARIA AWARENESS IN CAPITAL DECISION : ANALYSIS OF CHOICES BETWEEN CONVENTIONAL AND SHARIA FINANCING - Putri Balqist; Ayu Mariani; Rizfa Aryanti; Mohamad Arif (UIN MAHMUD YUNUS BATUSANGKAR, 2026)
Micro, small, and medium enterprises (MSMEs) in Batam City play an important role in the local economy. However, they still face challenges when making decisions related to capital financing. Although sharia-compliant financing options are available, many MSMEs tend to prefer conventional financing because it is seen as faster and more convenient. This study aims to explore how sharia awareness affects MSMEs' decisions regarding capital sources and to identify the factors influencing these decisions. The research employs a descriptive qualitative approach, utilizing in-depth interviews with eight informants from Islamic financial institutions and MSMEs in Batam City. Data were analyzed using the Miles and Huberman model. The results reveal that MSMEs show varying degrees of awareness about sharia principles. Although the principles of interest free (riba-free) and halal financing are regarded as important, practical considerations tend to dominate decision-making. Lack of understanding about sharia financing principles and procedures is a significant obstacle. The study recommends enhanced training and education on sharia financing to enable MSMEs to make more informed and rational financing decisions.